Underdetermined DOA estimation exploiting the higher‐order cumulants of harmonic steering vector with time‐modulated arrays - Yue Ma; Chen Miao; Yue‐Hua Li; Wen Wu (IET Signal Processing)
Abstract Time‐modulated arrays (TMAs) have been widely studied owing to their convenient control mode and simple structure. Although direction‐of‐arrival (DOA) estimation based on TMA has garnered considerable attention, underdetermined DOA estimation in TMA is yet to be studied. In this study, a novel method is proposed for underdetermined DOA estimation based on the higher‐order cumulants of harmonic signal in a TMA. The periodic modulation of radio‐frequency switches leads to a TMA generating harmonics in space. Cumulants of harmonic statistics can be used for DOA estimation, and with higher‐order harmonics cumulants, underdetermined DOA estimation can be realised with a TMA using the multiple signal classification method, and the degree of freedom can be improved further. Another advantage of the proposed method is its simple structure, which only requires one receiver with several filters. Numerical simulations show that the proposed method can achieve good resolution and precision performance.